Emergency hospital care for adults with suspected seizures in the NHS in England 2007–2013: a cross-sectional study. Issue 10 (21st October 2018) - Dickson, Jon Mark; Jacques, Richard; Reuber, Markus; Hick, Julian; Campbell, Mike J; Morley, Rebeka; Grünewald, Richard A
Abstract : Aims: To quantify the frequency, characteristics, geographical variation and costs of emergency hospital care for suspected seizures. Design: Cross-sectional study using routinely collected data (Hospital Episode Statistics). Setting: The National Health Service in England 2007–2013. Participants: Adults who attended an emergency department (ED) or were admitted to hospital. Results: In England (population 2011: 53.11 million, 41.77 million adults), suspected seizures gave rise to 50 111 unscheduled admissions per year among adults (≥18 years). This is 47.1% of unscheduled admissions for neurological conditions and 0.71% of all unscheduled admissions. Only a small proportion of admissions for suspected seizures were coded as status epilepticus (3.5%) and there were a very small number of dissociative (non-epileptic) seizures. The median length of stay for each admission was 1 day, the median cost for each admission was £1651 (2175) and the total cost of all admissions for suspected seizures in England was £88.2 million (116.2 million) per year. 16.8% of patients had more than one admission per year. There was significant geographical variability in the rate of admissions corrected for population age and gender differences and some areas had rates of admission which were consistently higher than the average. Conclusions: Our data show that suspected seizures are the most common neurological cause of admissions to hospital in England, that readmissions are common and that there is significant geographical variability in admission rates. This variability has not previously been reported in the published literature. The cause of the geographical variation is unknown; important factors are likely to include prevalence, deprivation and clinical practice and these require further investigation. Dissociative seizures are not adequately diagnosed during ED attendances and hospital admissions.